SOSIALISASI GERAKAN ORGANISASI BENCANA BERBASIS SYARI’AT ISLAM KEPADA SANTRI DAYAH AHLUSSUNAH WAL-JAMA’AH ANUWARUL BABISSALAM ACEH BARAT - Taufiq Akbar; Muhammad Nurdin; Muhammad Syafik; Mohamad Gazali (Universitas Teuku Umar, 2019)
Natural disaster realize us with the greatness of Allah SWT. However, human being always neglect and did wrongdoing that cause this earth to be labile. Therefore, the role of Dayah that yield santri with adequate knowledge in religion. Santri also prepared with disaster material. Thus, they are able to implemented the disaster mitigation and give preach for disaster casualties that experience trauma and depression. The aim of this activity is to give the socialization includng preach regarding disaster based Holy Qur’an and Hadist. The stage of held including (1) the socialization and preach related disaster, (2) to tell the positive and negative impact from natural disaster, (3) to form Focus Group Discussion about disaster organization movement based on islamic sharia for sustainablity and information media. In the socialization of disaster organization movement based on islamic sharia is begun to give preach regarding disaster. Subsequently, we conducted focus group discussion for forming the organization of disaster mujahidin. It is undertake as effort of PKM sustainablity.